Odpowiedź:
zad 5
a)
√2 * √18 = √(2 * 18) = √36 = √6² = 6
b)
√(0,04 * 81) + 1/5 * (∛25)³ = √324 + 1/5 * 25 = 18 + 5 = 23
c)
[(√17)² - ∛343 ] : ∛(1/125) = ( 17 - 7) : 1/5 = 10 : 1/5 = 10 * 5 = 50
zad 6
a)
√18 : √(2/9) = √(18 : 2/9) = √(18 * 9/2) = √(9 * 9) = √9² = 9
b)
3√32 - √18 - √8 = 3√(16 * 2) - √(9 * 2) - √(4 * 2) = 3 * 4√2 - 3√2 - 2√2 =
= 12√2 - 5√2 = 7√2
c)
(4∛24 - ∛3 + ∛81) : ∛3 = 4∛(24/3) - ∛(3/3) + ∛(81/3) = 4∛8 - 1 + ∛27 =
= 4 * 2 - 1 + 3 = 8 + 2 = 10
zad 7
a)
6/√3 = 6√3/(√3 * √3) = 6√3/√3² = 6√3/3 = 2√3
b)
(√12 - 5)/√3 = (√12 - 5) * √3/(√3 * √3) = [√(12 * 3) - 5√3]/√3² = (√36 - 5√3)/3 =
= (6 - 5√3)/3